Fetal Ovarian Torsion Presenting with Fetal Abdominal Solid Mass and Ascites - Mutlu Sütcüoğlu, Bengü; Karçaaltıncaba, Deniz; Guler, Ismail (Zeitschrift für Geburtshilfe und Neonatologie, 2022)
Fetal ovarian torsion is quite a rare event during the antenatal period and usually seen because of an ovarian cyst complication. In this case report, we present a case of fetal ovarian torsion without any ovarian cyst or underlying detectable causes. A 27-year-old primigravid woman with no significant past medical history had a routine prenatal ultrasound at 30 weeks’ gestation. The ultrasound showed abdominal ascites and a 47×42-cm intraabdominal solid diffuse mass at the left side under the stomach. Doppler examination showed no blood flow on the mass. Paracentesis was performed, cytological examination reported no abnormality. Based on these findings, the diagnosis was thought to be fetal ovarian torsion. There is lack of consistent recommendations to guide the prenatal and the postnatal management of cases with in-utero diagnosis of ovarian torsion. A “wait-and-see” policy is usually preferred, as in our case.
Keywords: benign disease of ovarian fallopian tubes; case report; ultrasound; perinatal diagnosis; fetal ovarian torsion